Test Anxiety Among College Students With Specific Reading Disability (Dyslexia): Nonverbal Ability and Working Memory as Predictors. (July 2015) - Nelson, Jason M.; Lindstrom, Will; Foels, Patricia A.
Test anxiety and its correlates were examined with college students with and without specific reading disability (RD; n = 50 in each group). Results indicated that college students with RD reported higher test anxiety than did those without RD, and the magnitude of these differences was in the medium range on two test anxiety scales. Relative to college students without RD, up to 5 times as many college students with RD reported clinically significant test anxiety. College students with RD reported significantly higher cognitively based test anxiety than physically based test anxiety. Reading skills, verbal ability, and processing speed were not correlated with test anxiety. General intelligence, nonverbal ability, and working memory were negatively correlated with test anxiety, and the magnitude of these correlations was medium to large. When these three cognitive constructs were considered together in multiple regression analyses, only working memory and nonverbal ability emerged as significant predictors and varied based on the test anxiety measure. Implications for assessment and intervention are discussed.